Public and Private Investment and the Convergence of Per Capita Incomes in Developing Countries - Khan, Mohsin; Kumar, Manmohan (Washington, D.C. : International Monetary Fund, 1993)
This paper examines the extent to which there has been convergence in real per capita incomes across developing countries during the last two decades. In the analysis particular emphasis is placed on the separate roles played by private and public sector investment in determining both the extent and the speed of convergence. The paper also considers the importance of the stock of human capital, trade orientation, and foreign direct investment in the long-run growth process. Empirical tests are carried out for a large sample of 95 developing countries over the period 1970-90. The results provide support for the notion of differential effects of public and private investment on long-term growth, as well as for the convergence hypothesis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet